Influence of hydrogen on softened heat-affected zones during in-situ slow strain rate testing in advanced high-strength steel welds. (1st April 2021) - Park, Hanji; Park, Cheolho; Lee, Junghoon; Kang, Namhyun; Liu, Stephen
Graphical abstract: Highlights: Narrow softened heat affected zone with hydrogen led to premature rupture. Wide softened zone caused fracture regardless of hydrogen charging. The base metal was fractured after SSRT in the hydrogen free environment. Martensite–austenite constituents increase hydrogen embrittlement sensitivity. Crack involved by hydrogen-enhanced localised-plasticity and hydrogen-induced voids. Abstract: Hydrogen stress cracking (HSC) of weldments should be evaluated as it occurs under environmental stress. This study investigated HSC reactions with regard to microstructures and hardness distribution in the transverse cross sections of welds deposited on an advanced high-strength steel through in-situ slow-strain rate testing (SSRT). SSRT in a hydrogen-free environment led to the fracture of the base metal, although a narrow and softened heat-affected zone (HAZ) was observed. However, during in-situ hydrogen charging SSRT, stress triaxiality increased in the softened inter-critical HAZ due to hydrogen trapped, and premature rupture was initiated from hydrogen-promoted voids with enhanced plasticity.